Rayong 3: Excepcional acogida de una variedad de yuca para almidon - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1991)
The success of Thailand`s cassava var. Rayong 3 is highlighted, particularly between cassava starch producers. Compared with Rayong 1, its fresh root yield is almost the same, starch production is higher, and drying time is shorter (2 vs. 3 days). Farmers planting Rayong 3 increased their revenues by at least 10-15 percent. Comparative data are provided for both var. regarding different agronomic characteristics. An innovative approach was adopted to accelerate the rate of diffusion of Rayong 3: free planting material (600-1200 cuttings) was provided to groups of 15 farmers with medium-sized farms (5-10 ha) for about 0.2 ha. The new var. now covers more than 5 percent of Thailand`s cassava producing area. Commercial processors have also participated in this process. (CIAT)